Infestation of guava by Anastrepha fraterculus (Diptera: Tephritidae): preferred ripening stages and influence of fruit peel coloration - De Oliveira, Flavia Queiroz [UNESP]; Boica Junior, Arlindo Leal [UNESP]; Zamboni Costa, Maria de Lourdes; Batista, Jacinto de Luna; Costa, Karen Zamboni; Melges Walder, Julio Marcos [UNESP] (Tubitak Scientific &technical Research Council Turkey, 2015)
The current study aimed to verify the preferred guava fruit ripening stage for egg laying by Anastrepha fraterculus (Diptera: Tephritidae) and to determine the influence of peel coloration of the fruits of 2 cultivars on infestation. The cultivars used were Paluma and Seculo XXI. The infestation level was evaluated in cages, considering 2 conditions: multiple-choice and nonchoice tests. The infestation levels of A. fraterculus differed between the green and the green-ripe stages in the multiple-choice test. In Paluma fruits with the nonchoice test, the infestation was highest during the ripe stage. There were no differences in infestation levels of A. fraterculus between the green and the green-ripe stages in Seculo XXI. In general, the green-ripe and the ripe stages were preferred for egg laying by A. fraterculus. In Paluma fruits there were significant correlations of infestation levels of A. fraterculus with luminosity (L) and chromaticity (C) in the nonchoice assay. In Seculo XXI fruits there was a significant correlation of infestation levels of A. fraterculus with color angle (h) in the nonchoice assay. No correlation was found between theses parameters in the multiple-choice test.
Keywords: Fruit flies; Myrtaceae; Preference-performance